2020
DOI: 10.7554/elife.50670
|View full text |Cite
|
Sign up to set email alerts
|

GLI transcriptional repression regulates tissue-specific enhancer activity in response to Hedgehog signaling

Abstract: Transcriptional repression needs to be rapidly reversible during embryonic development. This extends to the Hedgehog pathway, which primarily serves to counter GLI repression by processing GLI proteins into transcriptional activators. In investigating the mechanisms underlying GLI repression, we find that a subset of GLI binding regions, termed HH-responsive enhancers, specifically loses acetylation in the absence of HH signaling. These regions are highly enriched around HH target genes and primarily drive HH-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…We next examined published ChIP-seq data to examine whether Rspo2 , Notum , Wnt4 and Wnt11 were likely to be direct target genes of Gli and Foxf1 transcription factors. We used previously published Gli3-3xFlag ChIP from E10.5 limb buds and Foxf1 ChIP from E18.5 lungs ( Dharmadhikari et al, 2016 ; Lex et al, 2020 ); these datasets are the most similar to tracheal chondrocytes currently available. We also examined previously published ATAC-seq and H3K4me3 ChIP-seq performed in the E9.5 cardiopulmonary foregut progenitors to help identify active promoter and enhancer regions ( Steimle et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next examined published ChIP-seq data to examine whether Rspo2 , Notum , Wnt4 and Wnt11 were likely to be direct target genes of Gli and Foxf1 transcription factors. We used previously published Gli3-3xFlag ChIP from E10.5 limb buds and Foxf1 ChIP from E18.5 lungs ( Dharmadhikari et al, 2016 ; Lex et al, 2020 ); these datasets are the most similar to tracheal chondrocytes currently available. We also examined previously published ATAC-seq and H3K4me3 ChIP-seq performed in the E9.5 cardiopulmonary foregut progenitors to help identify active promoter and enhancer regions ( Steimle et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…ChIP-Seq analysis was performed on the following published datasets: (1) Foxf1 ChIP on dissected E18.5 lung ( , Dharmadhikari et al, 2016 ); (2) Gli3-3xFlag ChIP on dissected E10.5 limb buds ( , Lex et al, 2020 ); and (3) ATAC-seq and H3K4me3 ChIP performed on E9.5 cardiopulmonary progenitors ( , Steimle et al, 2018 ). These datasets were reprocessed using CSBB, and for visualization purposes, bigwig files were generated using deepTools (BamCoverage function) ( Ramírez et al, 2016 ) from bam files.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent activation can then occur from either GliA or additional TFs. GliR function is primarily carried out by Gli3 and is indispensable for proper Hh-dependent patterning (Litingtung and Chiang 2000;Wang et al 2000;Oosterveen et al 2012;Lex et al 2020). Recent studies in the limb, which is dependent upon Gli3R for proper patterning, have shown that not all GBMs are created equal.…”
Section: Gli3 Functions As An Activator Within the Developing Craniofmentioning
confidence: 99%
“…Recent studies in the limb, which is dependent upon Gli3R for proper patterning, have shown that not all GBMs are created equal. While some GBMs appear to be completely dependent on a Hh input, others remain 'stable' with Gli3 occupancy occurring independent of the morphogen (Lex et al 2020). However, to date, no classification system of GBM utilization in the face has been established.…”
Section: Gli3 Functions As An Activator Within the Developing Craniofmentioning
confidence: 99%
“…Although Gli family members bind to same consensus DNA sequences, the differential roles of GliA and GliR in sculpting tissues could likely arise from context-dependent cis-regulation of targets by coactivators/repressors (Oosterveen et al, 2012). Alternatively, tissue-specific regulation of enhancer activity could regulate Gli-mediated repression (Lex et al, 2020). The effects of ciliary loss of Gpr161 are dependent on requirements of the tissues on GliR levels as follows:…”
Section: Gpr161 Ciliary Pools Regulate Hh Repression Mediated Morpho-phenotypic Spectrummentioning
confidence: 99%